Constitutional amendment in Africa and the limitation of presidential terms. : Contribution to the review of constitutional amendment power. - (:unkn) unknown (My University, 2022)
African countries have been experiencing an increasing number of constitutional amendments, mainly affecting the presidential term limit clause. Leaders, who initiate them, seek to facilitate their re-election. Such reformist inclinations lead to major political and social crises. From the political actors, civil society organisations and citizen movements point of view, the presidential term limit clause is a key feature of constitutions and as such it should not be the subject of constitutional amendments. This thesis aims at demonstrating that constitutional amendment power is not absolute power. It must comply with two requirements. The first is formal. The amendment process provided by constitutions needs to be followed. The second is an objective. The duty of constitutional amendment power is to consolidate the institutional system by preserving its founding principles. These form the basic structure of constitutions. In Africa, it appears that these two requirements are not always observed when amending constitutions. This research also highlights that at both national and regional levels, there is a set of original mechanisms supervising constitutional amendment power, which are political and jurisdictional, but still in their infancy.
Keywords: African Research